Analysis of information providing for antihypertensive medicines according to the data of Ukrainian web services - O. M. Zaliska; V. S. Huz (The State Expert Center of the Ministry of Health of Ukraine, 2023)
The digitalization of the pharmaceutical field provides new opportunities to meet patient's needs and to improve communications, which is important for pharmacies. According to the Law of Ukraine dated 17.09.2020 «On Amendments to Article 19 of the Law of Ukraine "On Medicines" regarding the implementation of electronic retail trade of medicinal products» and Article 81 of the Law of Ukraine «On Medicines» dated 28.07.2022), pharmacies were allowed to carry out electronic retail trade of pharmaceuticals on the condition that information about the right to online trade is entered in the Licensing Register for the manufacture of medicines The aim was the analysis and detailed study of the information content of sections of web services of pharmacies and web portals of Ukraine using the example of drugs for the treatment of arterial hypertension and substantiating the need for unification of information for patients. The basis of our analysis was information from 18 web services of pharmacy chains and 5 Internet portals for booking medicines. The analysis of the information support revealed that the most common filters for searching drugs for the treatment of arterial hypertension on resources were: medicine price scale, manufacturer, form of release and dosage. The results of the structural analysis of information showed that the following parameters are available on all sites and platforms: trade name of the medicinal product, price, form of release, dosage and quantity in the package. The information about the manufacturer is presented on 66% of pharmacy web services and 60% of web platforms. Only 28% of the pharmacy web services and 60% web platforms inform patients about the dispensing of prescription drugs. Identified differences in the information content of websites and web platforms require the unification of information for patients with arterial hypertension according to such parameters as: prescription leave; dispensing by e-prescription, with an emphasis on application features; the participation of pharmacies in social programs, especially reimbursement, which will contribute to the optimization of information and educational provision of patients for the rational use of drugs for chronic non-infectious diseases.